(untitled) (World Bulletin of Management and Law, 2024)
International marketing has become a critical element for businesses seeking to expand and compete in the global marketplace. This article investigates the diverse marketing strategies companies adopt to cater to different international markets, exploring the impact of cultural, economic, legal, and political factors on their decision-making processes. It discusses the differences between standardization and adaptation in marketing strategies, examining how companies balance global branding with local responsiveness. Through case studies of successful global companies, the article provides insights into how businesses can navigate challenges and leverage opportunities in international markets. The findings emphasize that an adaptive and culturally sensitive approach to international marketing often leads to better market penetration and long-term success.